2023
DOI: 10.22146/jtbb.78346
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of Rhizospheric Bacteria Associated with Canna Plant for Production of Maltooligosaccharide Amylase

Rina Dwi Agustiani,
Oedjijono Oedjijono,
Nanik Rahmani
et al.

Abstract: The objectives of the study were to isolate amylolytic bacteria from the rhizosphere and plant tissue of Canna edulis Ker., as well as litter; to know oligosaccharide compounds produced from starch hydrolyzed by the bacterial enzymes, and to identify the amylolytic bacteria based on phenetic and 16S rRNA gene sequences. From the rhizosphere, Canna plant tissue, and litters obtained thirty-two amylolytic bacterial isolates. Eight isolates (TH6, TH7, T5, T10, D2, D3, A3, S1) produced high clear zone diameters ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It has enormous economic significance; for example, Bacillus toyonensis BCT-7112 spores have been utilized as probiotic supplements in animal nutrition [15]. It was previously reported to exhibit plant growth promotion, biodegradation, and probiotic and biocontrol properties [16][17][18]. Its biocontrol properties are rarely reported; however, Wang et al reported its toyoncin-producing ability.…”
Section: Introductionmentioning
confidence: 99%
“…It has enormous economic significance; for example, Bacillus toyonensis BCT-7112 spores have been utilized as probiotic supplements in animal nutrition [15]. It was previously reported to exhibit plant growth promotion, biodegradation, and probiotic and biocontrol properties [16][17][18]. Its biocontrol properties are rarely reported; however, Wang et al reported its toyoncin-producing ability.…”
Section: Introductionmentioning
confidence: 99%